Graphite-molybdenum disulfide synergistic lubrication Fe-Cu-based self-lubricating material as well as preparation method and application thereof

The Fe-Cu based self-lubricating material with graphite-molybdenum disulfide synergistic lubrication solves the performance stability problem of single lubricating phase materials under a wide temperature range and variable load conditions, achieves low friction coefficient, low wear rate and excellent tribological properties, is suitable for a variety of mechanical structures, and is low-cost.

CN120665634APending Publication Date: 2025-09-19UNIV OF JINAN +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510567501.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

In the existing technology, iron-based self-lubricating materials with a single lubricating phase have insufficient performance stability under a wide temperature range and variable load conditions. Moreover, after adding lubricants, the material cost is high and the mechanical properties are reduced, making it difficult to achieve the synergistic effect of changing the proportions of various lubricants.

Method used

The Fe-Cu based self-lubricating material with graphite-molybdenum disulfide as the synergistic lubricating phase is prepared by a vacuum sintering process. The graphite exists in a free form, and MoS2 reacts with iron to form a FeS lubricating phase, forming a material with low friction coefficient and high wear resistance.

Benefits of technology

The material has low friction coefficient, low wear rate, excellent tribological properties and mechanical properties under the condition of no liquid lubricant. The preparation method is simple and low cost, and it is suitable for mechanical structures under various working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120665634A_ABST
    Figure CN120665634A_ABST
Patent Text Reader

Abstract

The invention discloses a graphite-molybdenum disulfide synergistic lubrication Fe-Cu-based self-lubricating material as well as a preparation method and application thereof, and belongs to the technical field of self-lubricating materials. The Fe-Cu-based self-lubricating material with graphite-molybdenum disulfide synergistic lubrication is prepared from the following components in percentage by mass: 2 to 10 weight percent of copper powder, 0.2 to 2 weight percent of zinc stearate, 1.5 to 6 weight percent of molybdenum disulfide, 1 to 7 weight percent of graphite and the balance of Fe powder. Wherein MoS2 reacts with an iron element to generate a new FeS lubricating phase, graphite exists in a Fe matrix in a free graphite form, and the Fe-based composite material has the characteristics of low friction coefficient, high wear resistance and the like due to double lubricating components. The lubricant can be applied to mechanical structures without liquid lubricants or in which the liquid lubricants are insufficient to provide enough lubrication, part abrasion and equipment energy consumption are reduced, the lubricant has excellent tribological performance, the preparation method is simple, technological parameters in the preparation process are easy to control, and meanwhile the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of self-lubricating materials, and in particular relates to a Fe-Cu based self-lubricating material with synergistic lubrication of graphite and molybdenum disulfide, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] Across various engineering fields, lubricating oils and greases are the most widely used lubricating media to improve lubrication between mechanical parts. However, in some special operating conditions and scenarios (such as vacuum, high temperature, food, and pharmaceutical applications), fluid lubricating media (such as lubricating oils and greases) are no longer suitable. To address these lubrication issues, solid self-lubricating materials have gradually become a focus of research. Iron-based self-lubricating materials have attracted considerable attention due to their excellent mechanical properties and cost advantages. They achieve self-lubricating mechanisms at the friction interface by introducing a solid lubricating phase. Existing research has shown that the introduction of single lubricating phases such as graphite, CeO2, MoS2, and CaF2 can effectively enhance the tribological and mechanical properties of the materials. Existing research has investigated the effects of MoS2 on the sintering behavior and mechanical properties of iron-based friction materials, finding that increasing MoS2 content improves the material's density, compressive strength, and mechanical properties, while also improving the material's wear performance. Existing research has also investigated the effects of CeO2 addition and green compact density on the properties of iron-based self-lubricating bearing materials, finding that adding an appropriate amount of CeO2 can improve the material's overall performance. However, the performance stability of single-phase lubricating systems over a wide temperature range and under variable load conditions remains a bottleneck. In recent years, research has shifted to exploring the synergistic effects of multiple lubricating phases. Existing studies have compared the effects of the combined addition of MoS2 and BN on the tribological properties of nickel-based materials, finding that a ratio of 5% MoS2 + 5% BN exhibits optimal anti-wear properties. Furthermore, the synergistic effect of 3% CaF2 and 3% MoS2 in prepared Fe-Ni composites has been studied, resulting in excellent tribological properties across the room-temperature to high-temperature range. While these studies have demonstrated the feasibility of composite lubrication, existing technologies still have significant limitations. First, the total amount of lubricant varies within a certain range, and the content of each lubricant is fixed, making it difficult to determine whether a synergistic effect exists when the ratios of the lubricants are varied. Second, while the addition of lubricating phases to these matrices improves the self-lubricating and friction and wear properties of the materials, this increases the cost of self-lubricating wear-resistant materials and reduces their overall mechanical properties, potentially leading to serious engineering failures. Therefore, balancing the mechanical and wear properties of self-lubricating materials remains a significant challenge. Summary of the Invention

[0004] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide a Fe-Cu based self-lubricating material with graphite-molybdenum disulfide synergistic lubrication, and a preparation method and application thereof. The Fe-Cu based self-lubricating material with graphite-MoS2 synergistic lubrication provided by the present invention is a Fe-Cu based self-lubricating material with the advantages of simple process, low cost, low friction coefficient, and excellent mechanical properties.

[0005] The present invention relates to an Fe-Cu-based self-lubricating material with graphite-molybdenum disulfide as a synergistic lubricating phase. The material's chemical components, in percentage by weight, are: 5 wt.% copper, 0.8 wt.% zinc stearate, 0-6 wt.% molybdenum disulfide, 0-7 wt.% flake graphite, and the remainder Fe powder. The ingredients are dry-blended in a planetary ball mill to obtain an alloy powder, which is then pressed into a green compact using a mold and sintered in a vacuum process to produce the novel Fe-Cu-based self-lubricating material. MoS2 reacts with iron to form a new FeS lubricating phase, while graphite exists as free graphite in the Fe matrix. These dual lubricating components give the Fe-based composite material a low friction coefficient and strong wear resistance. The present invention can be applied to mechanical structures where liquid lubricants are not available or insufficient to provide sufficient lubrication, reducing component wear and equipment energy consumption. The material exhibits excellent tribological properties, is simple to prepare, and process parameters are easily controlled during the preparation process. The material is also low in cost.

[0006] In order to achieve the above object, the technical solution of the present invention is: In the first aspect, the present invention provides an Fe-Cu based self-lubricating material with graphite-molybdenum disulfide synergistic lubrication, which comprises the following components in mass percentage: 2-10 wt.% copper powder, 0.2-2 wt.% zinc stearate, 0~6 wt.% molybdenum disulfide, 0~7 wt.% graphite, and the rest Fe powder.

[0007] Furthermore, copper powder 2-10 wt.%, zinc stearate 0.2-2 wt.%, molybdenum disulfide 1.5-6 wt.%, graphite 1-7 wt.%, and the rest is Fe powder.

[0008] Furthermore, copper powder 4-6 wt.%, zinc stearate 0.5-1.0 wt.%, molybdenum disulfide 1.5~6 wt.%, graphite 1~7 wt.%, and the rest is Fe powder.

[0009] Furthermore, copper powder 4-6 wt.%, zinc stearate 0.5-1.0 wt.%, molybdenum disulfide 3-4.5 wt.%, graphite 2.5-4 wt.%, and the rest is Fe powder.

[0010] Furthermore, copper powder 4-6 wt.%, zinc stearate 0.5-1.0 wt.%, molybdenum disulfide 3-3.5 wt.%, graphite 3.5-4 wt.%, and the rest is Fe powder.

[0011] In one or more embodiments, the copper powder is atomized spherical Cu powder with a particle size of 100-500 mesh, preferably 200-300 mesh, and a purity of 99.9%.

[0012] The atomized spherical Cu powder particles have a smooth surface and strong fluidity. In powder metallurgy processes, they can achieve uniform powder spreading, reduce voids, and improve product density and mechanical properties. They are also conducive to the preparation of high-density green bodies, reducing sintering shrinkage and reducing internal defects.

[0013] Zinc stearate can improve the compression properties of the powder and act as a demoulding lubricant. It will evaporate during the sintering process and will not affect the composition design of the material.

[0014] In one or more embodiments, the purity of molybdenum disulfide is 99.9%, and the particle size is 500-1000 mesh, preferably 700-900 mesh.

[0015] In one or more embodiments, the graphite is high-purity flake graphite powder with a purity of 99.9% and a particle size of 500-1000 mesh, preferably 700-900 mesh.

[0016] The hexagonal layered structure of graphite makes it easy to slip under shear force, while the thin flake morphology of scaly graphite can be peeled off more efficiently along the base surface, forming a continuous lubricating film and reducing the material's friction coefficient.

[0017] In one or more embodiments, the reduced iron powder has a particle size of 100-500 mesh, preferably 200-400 mesh, and a purity of 99.9%.

[0018] In a second aspect, the present invention provides a method for preparing a Fe-Cu based self-lubricating material with graphite-molybdenum disulfide synergistic lubrication, comprising the following steps: Copper powder, zinc stearate, molybdenum disulfide, graphite and Fe powder are mixed to obtain alloy powder, which is then pressed into a green body using a mold and manufactured through a sintering process.

[0019] In one or more embodiments, mixing is performed in a ball mill at a rotation speed of 100-500 r / min, preferably 200-300 r / min, a mixing time of 0.5-5 h, preferably 1-2 h, and a ball-to-material ratio of 1:8-10.

[0020] In one or more embodiments, during mold pressing, the unit pressing pressure is 400-600 MPa, the holding time is 1-5 min, and a sample with a diameter of 10-30 mm is produced after demolding.

[0021] In one or more embodiments, the sintering process is a vacuum sintering process, the sintering temperature is 900-1400°C, preferably 1050-1250°C, the heating rate is 5-10°C / min, and the holding time is 0.5-3 h.

[0022] Vacuum sintering is used to prevent oxidation of Fe-based materials during high-temperature sintering, ensuring that the sintering process does not affect the final performance of the material.

[0023] In a third aspect, the present invention provides the use of the above-mentioned Fe-Cu based self-lubricating material with synergistic lubrication of graphite and molybdenum disulfide in a mechanical structure under working conditions when there is no liquid lubricant or the liquid lubricant is insufficient.

[0024] One or more of the above technical solutions have the following advantages or beneficial effects: (1) The Fe-Cu based self-lubricating material prepared by the present invention has a stable and low friction coefficient of 0.266 at room temperature and a low wear rate of 0.031 mm with solid lubricants such as graphite and sulfide existing in the material itself. 3 / (N·m), and has a high surface hardness (214.2 HV 0.2 ) and compressive strength (569.3 MPa), overcoming the difficulties that the traditional addition of a single solid lubricant content is too low to form a sufficient lubricating film on the friction pair surface, and too high a content will reduce the overall mechanical strength of the base material.

[0025] (2) The Fe-Cu based self-lubricating material prepared by the present invention uses fewer alloying elements and has a simple process. At the same time, the solid lubricant used is inexpensive and has excellent mechanical properties and friction and wear properties, which reduces production costs and is conducive to the large-scale preparation of Fe-Cu based self-lubricating materials and the expansion of their application fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0027] Figure 1 SEM photos of the raw materials required for preparing Fe-Cu-based self-lubricating materials in Examples 1-6 of the present invention; wherein (a) is reduced iron powder, (b) is atomized spherical copper powder, (c) is MoS2 powder, and (d) is flake graphite powder; Figure 2 This is the XRD phase diagram analysis of Example 4 before and after sintering; Figure 3 The friction coefficient curves and wear rate comparison diagrams of Examples 1-6 of the present invention are shown; Figure 4 The 3D surface profile and wear scar interface size diagram of the Fe-Cu based self-lubricating material of Example 1-2 of the present invention after friction and wear; Figure 5 3D surface profiles and wear scar interface dimensions of the Fe-Cu based self-lubricating materials of Examples 3-6 of the present invention after friction and wear; Figure 6 These are SEM photographs of the wear surfaces of the Fe-Cu based self-lubricating materials of Examples 1-6 of the present invention; wherein, (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Example 5, and (f) is Example 6. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0029] Example 1 The Fe-Cu based self-lubricating material comprises the following components by mass percentage: 88.2% reduced Fe powder, 5% atomized spherical Cu powder, 0%-6% high purity flake graphite powder, 0%-6% high purity MoS2 powder, and 0.8% zinc stearate powder. The micromorphology of the raw materials used is as follows: Figure 1 As shown, Figure 1 (a) reduced iron powder, 200-400 mesh; Figure 1 (b) atomized spherical copper powder, 200-300 mesh; Figure 1 (c) MoS2 powder, 800 mesh; Figure 1 (d) is flake graphite powder, 800 mesh.

[0030] Powder mixing: The above powders were proportioned according to Table 1 and mechanically alloyed. The prepared powders were then placed in a planetary mixer for mixing. The ball mill speed was set at 250 r / min, the mixing time was 1.5 h, and the ball-to-material ratio was 1:10. Example 1 is a base sample, i.e., a sample without the addition of a solid lubricant; Example 2 is a sample with the addition of 1% graphite and 6% MoS2 as a solid lubricant; Example 3 is a sample with the addition of 2.5% graphite and 4.5% MoS2 as a solid lubricant; Example 4 is a sample with the addition of 4% graphite and 3% MoS2 as a solid lubricant; Example 5 is a sample with the addition of 5.5% graphite and 1.5% MoS2 as a solid lubricant; and Example 6 is a sample with the addition of 7% graphite as a solid lubricant.

[0031] The compaction was performed using a 60 T universal testing hydraulic press. The specific test parameters were as follows: 10 g of mixed powder was weighed and placed in a compacting die. The unit compaction pressure was 500 MPa, the holding time was 2 min, and a sample with a diameter of 20 mm was prepared after demolding.

[0032] Sintering: The sintering temperature is 1100℃. At the same time, in order to prevent oxidation during the sintering process, a vacuum tube sintering furnace is used to sinter the sample. The heating rate is 8℃ / min, the holding time is 1 h, and the sample is cooled with the furnace.

[0033] Table 1

[0034] XRD phase diagram analysis takes Example 4 as an example, the phase composition before and after sintering is as follows Figure 2 As shown. Figure 2 (a) It can be seen that before sintering, the sample is mainly composed of Fe, Cu, C, and MoS2 phases, among which the diffraction peak of MoS2 phase is higher. Figure 2 (b) The XRD pattern of the sintered sample shows no diffraction peaks for the MoS2 phase, but instead displays diffraction peaks for FeS and Fe3Mo3C. Meanwhile, the diffraction peak for element C is significantly weakened, indicating that C primarily dissolves in Fe and forms the Fe3Mo3C phase with the Mo produced by the decomposition of MoS2. However, a small amount of elemental graphite is still present. This suggests that the simultaneous addition of MoS2 and graphite as solid lubricants transforms the lubricating phase of the sintered sample into two components: FeS and free graphite. Furthermore, the solid solution strengthening effect of Mo significantly improves the mechanical properties of the material.

[0035] In Examples 1-6, dry sliding friction tests were conducted at room temperature using a GCr15 cylindrical pin measuring 5.6 × 8.5 mm in diameter. The experimental parameters were: frequency: 2 Hz, stroke: 9 mm, applied load: 50 N, and wear time: 30 min. The friction coefficient was dynamically acquired, and the wear morphology was captured using a white-light interferometer. The images were then imported into data processing software (such as Gwydditon) to measure the wear scar depth, width, wear volume, and three-dimensional profile. Finally, friction coefficient and wear profile curves were generated using graphics software (such as Origin).

[0036] The test data of all the above examples are shown in Table 2.

[0037] Table 2 Properties of Fe-Cu based self-lubricating materials obtained in the above embodiments Table 2

[0038] According to the experimental results in Table 2 and combined with Figure 3The friction coefficient curve shows that the Fe-Cu based self-lubricating material of the present invention has relatively excellent mechanical properties (compressive strength greater than 500 MPa, hardness greater than 200 HV 0.2 ), and has good friction and wear resistance (friction coefficient as low as 0.266, wear rate as low as 0.031 mm 3 / (N·m)). Examples 3, 4, and 5, which used a graphite-MoS2 mixed solid lubricant, all significantly reduced their friction coefficients compared to the base sample of Example 1, and their mechanical properties were significantly improved. Furthermore, compared to the samples of Examples 2 and 6, which added only one solid lubricant, their friction coefficients did not differ significantly, but their mechanical properties were significantly improved.

[0039] Figure 4 and Figure 5 It can be seen that compared with the base material of Example 1, the mixed addition of a certain amount of graphite and MoS2 can effectively reduce the wear scar width and wear scar depth of the sample. At the same time, compared with the samples of Example 2 and Example 6 in which only one solid lubricant is added, the wear width and depth of Examples 3-5 are improved to a certain extent, and the wear resistance is significantly improved. In particular, the wear scar depth of the sample of Example 4 is the lowest, its surface is relatively smooth as a whole, and the scratches are relatively shallow. The reason is that the synergistic lubrication of free graphite and FeS effectively improves the friction performance of the friction surface, so the surface after friction undergoes self-repair, and a good lubricating layer is formed on the friction surface. It can be seen that the Fe-Cu based self-lubricating material of the present invention has good friction and wear performance.

[0040] Figure 6 SEM images of the worn surfaces of Examples 1-6 after dry friction and wear tests. Figure 6 (a) is the SEM image of the wear surface of the substrate sample of Example 1. The friction surface has a varying number of furrows parallel to the sliding direction, and the furrow depth is relatively deep, indicating that abrasive wear is the main wear mechanism. The surface of the sample of Example 3 shows significant peeling, which is a characteristic of fatigue wear. Figure 6 (c) As shown; the friction morphology of the sample of Example 4 is significantly improved, showing a smooth and flat feature, with only shallow furrows, such as Figure 6 (d) shows that the synergistic lubrication effect of FeS and free graphite effectively inhibits the plowing effect. However, as the amount of MoS2 added further decreases, as shown in Figure 6As shown in (e), the friction surface of Example 5 begins to peel slightly, and the furrow depth increases. This is mainly due to the weakening of the strengthening effect of the Mo element, which leads to a decrease in the bonding strength between the soft phase and the matrix. It is worth noting that the samples with only graphite or MoS2 added as solid lubricants, namely Examples 2 and 6, have a significant increase in the number of peeling pits on the friction surface. At the same time, more oxide films are formed on the friction surface, which indicates that oxidation wear and fatigue wear are the main wear mechanisms. Figure 6 (b) and Figure 6 (d) Although the flaking wear debris can significantly reduce the friction coefficient of the material, the wear resistance of the material will be greatly reduced.

[0041] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A Fe-Cu based self-lubricating material with graphite-molybdenum disulfide synergistic lubrication, characterized in that: The invention comprises the following components in terms of mass percentage: 2-10 wt.% of copper powder, 0.2-2 wt.% of zinc stearate, 0-6 wt.% of molybdenum disulfide, 0-7 wt.% of graphite, and the rest of Fe powder.

2. The Fe-Cu based self-lubricating material according to claim 1, characterized in that: Copper powder 2-10 wt.%, zinc stearate 0.2-2 wt.%, molybdenum disulfide 1.5~6 wt.%, graphite 1~7 wt.%, and the rest is Fe powder.

3. The Fe-Cu based self-lubricating material according to claim 2, characterized in that: Copper powder 4-6 wt.%, zinc stearate 0.5-1.0 wt.%, molybdenum disulfide 1.5~6 wt.%, graphite 1~7 wt.%, and the rest is Fe powder.

4. The Fe-Cu based self-lubricating material according to claim 3, characterized in that: Copper powder 4-6 wt.%, zinc stearate 0.5-1.0 wt.%, molybdenum disulfide 3~4.5 wt.%, graphite 2.5-4 wt.%, and the rest is Fe powder.

5. The Fe-Cu based self-lubricating material according to claim 1, characterized in that: The copper powder is atomized spherical Cu powder with a particle size of 100-500 mesh; Preferably, the particle size of molybdenum disulfide is 500-1000 mesh; Preferably, the graphite is high-purity flake graphite powder with a particle size of 500-1000 mesh; Preferably, the particle size of the iron powder is 100-500 mesh.

6. A method for preparing the Fe-Cu based self-lubricating material with graphite-molybdenum disulfide synergistic lubrication according to any one of claims 1 to 5, characterized in that: The following steps are involved: Copper powder, zinc stearate, molybdenum disulfide, graphite and Fe powder are mixed to obtain alloy powder, which is then pressed into a green body using a mold and manufactured through a sintering process.

7. The preparation method according to claim 6, characterized in that The mixing is carried out in a ball mill at a rotation speed of 100-500 r / min, preferably 200-300 r / min, a mixing time of 0.5-5 h, preferably 1-2 h, and a ball-to-material ratio of 1:8-10.

8. The preparation method according to claim 6, characterized in that During mold pressing, the unit pressing pressure is 400~600MPa, the holding time is 1-5 min, and a sample with a diameter of 10-30 mm is made after demolding.

9. The preparation method according to claim 6, characterized in that The sintering process is a vacuum sintering process, the sintering temperature is 900-1400°C, preferably 1050-1250°C, the heating rate is 5-10°C / min, and the holding time is 0.5-3 h.

10. Use of the Fe-Cu based self-lubricating material with synergistic lubrication of graphite and molybdenum disulfide according to any one of claims 1 to 5 or the Fe-Cu based self-lubricating material with synergistic lubrication of graphite and molybdenum disulfide obtained by the preparation method according to any one of claims 6 to 9 in a mechanical structure in the absence of a liquid lubricant or in the absence of a liquid lubricant.